2017
DOI: 10.1111/cobi.12978
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters used in setting captive‐breeding quotas for Indonesia's breeding facilities

Abstract: Palabras Clave: conservación, criado en cautiverio, lavado, manejo, mercado de fauna

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Under CITES agreements, certified breeding farms are permissible for some species 3 , 14 16 . Breeding farms are approved to ostensibly reduce pressure from illegal poaching on wild populations and to assist in biodiversity conservation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Under CITES agreements, certified breeding farms are permissible for some species 3 , 14 16 . Breeding farms are approved to ostensibly reduce pressure from illegal poaching on wild populations and to assist in biodiversity conservation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Our vision for a new domain of applied conservation science is applicable to large carnivores and other systems in which academics and others hold governments and interest groups accountable (Janssen & Chng 2017). We accept that increased scrutiny will not often provide evidence for if, how, and why political interference occurred; rather, it will reveal if reported population data on which policy is based are unreliable.…”
mentioning
confidence: 99%
“…We found that pangolin leather products were still being traded in the US, although to a much lesser extent since the establishment of the zero export quota in 2000. In many countries corruption, and enforcement and monitoring issues, as well as inadequate protection of exploited species, increase the difficulties to assess the sustainability of the exotic skin trade (Janssen & Chng, 2017;Lyons & Natusch, 2011;Nijman, Shepherd, & Sanders, 2012). There are examples where the use of exotic skins can be sustainable and even beneficial for species conservation (see, e.g., MacGregor, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife laundering remains a core issue. In many countries corruption, and enforcement and monitoring issues, as well as inadequate protection of exploited species, increase the difficulties to assess the sustainability of the exotic skin trade (Janssen & Chng, 2017;Lyons & Natusch, 2011;Nijman, Shepherd, & Sanders, 2012). Ultimately, generalizations about this trade (see, e.g., Natusch et al, 2019) are unhelpful, as the potential for sustainably trading exotic leather is highly species (and country) dependent.…”
Section: Discussionmentioning
confidence: 99%